2010
DOI: 10.1080/00071668.2010.520302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein regime on meat quality traits and carcase nutrient content of broilers from two commercial genotypes

Abstract: 229, 199 and 182 g/kg and High: 266, 235 and 207 g/kg for starter, grower and finisher diets respectively). On d 21 and 42, initial protein solubility, DNA and myofibre density were determined. On d 42, breast meat samples were collected for meat quality analyses. 3. There were no genotype effects on pH(24), L*, a* or b* values. Thawing loss was higher in meat from the 708 than the 308 genotype. 4. Broilers given the low protein feeding regime had highest carcase fat, lowest pH(24) and palest meat. The low reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
8
1
1
Order By: Relevance
“…In a comparison of low-protein and normal-protein diets in broiler chickens, Collin et al (2003) found that low-protein diets caused a significant increase in the abdominal fat content percentage. Yalçin et al (2010) also found that feeding broiler chickens diets containing 19.2%, 16.6%, and 15.5% CP (low protein) led to an increase in total carcass fat deposition compared with chickens fed diets containing 22.9%, 19.9%, and 18.2% CP (the standard recommended by NRC [1994]) in the starter, grower, and finisher phases, respectively. Increasing dietary protein level in the diets of broiler chickens to 26.6%, 23.5%, and 20.7% in the starter, grower, and finisher phases led to a reduction in total carcass fat deposition compared with diets formulated according to NRC (1994) (Yalçin et al, 2010).…”
Section: Discusionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a comparison of low-protein and normal-protein diets in broiler chickens, Collin et al (2003) found that low-protein diets caused a significant increase in the abdominal fat content percentage. Yalçin et al (2010) also found that feeding broiler chickens diets containing 19.2%, 16.6%, and 15.5% CP (low protein) led to an increase in total carcass fat deposition compared with chickens fed diets containing 22.9%, 19.9%, and 18.2% CP (the standard recommended by NRC [1994]) in the starter, grower, and finisher phases, respectively. Increasing dietary protein level in the diets of broiler chickens to 26.6%, 23.5%, and 20.7% in the starter, grower, and finisher phases led to a reduction in total carcass fat deposition compared with diets formulated according to NRC (1994) (Yalçin et al, 2010).…”
Section: Discusionmentioning
confidence: 89%
“…Yalçin et al (2010) also found that feeding broiler chickens diets containing 19.2%, 16.6%, and 15.5% CP (low protein) led to an increase in total carcass fat deposition compared with chickens fed diets containing 22.9%, 19.9%, and 18.2% CP (the standard recommended by NRC [1994]) in the starter, grower, and finisher phases, respectively. Increasing dietary protein level in the diets of broiler chickens to 26.6%, 23.5%, and 20.7% in the starter, grower, and finisher phases led to a reduction in total carcass fat deposition compared with diets formulated according to NRC (1994) (Yalçin et al, 2010). Moreover, Jlali et al (2012) found that increasing dietary CP level from 17% to 23% in fat and lean broiler chickens from 21 to 63 days of age caused a significant reduction in abdominal fat deposition.…”
Section: Discusionmentioning
confidence: 89%
“…The higher amino acid endogenous losses and requirements to develop and maintain the digestive tract might be related to the more important abdominal fat deposition found in the birds fed the diluted diet. Yalçin et al. (2010) found that feeding broiler chickens diets containing 19.2, 16.6, and 15.5% CP (low protein) led to an increase in the total-carcass fat deposition, as compared with chickens fed diets containing 22.9, 19.9, and 18.2% CP in the starter, grower, and finisher phases, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…L'impact de l'aliment sur les caractéristiques du filet peut toutefois dépendre du type génétique, notamment de la capacité d'engraissement des animaux (Jlali et al 2012). D'une manière générale, l'impact de l'apport en protéines sur le pH et la qualité du filet apparaît comme variable et susceptible de dépendre de nombreux facteurs, liés aux caractéristiques des régimes ou à celles des animaux (Yalçin et al 2010, Lilly et al 2011, Zhao et al 2012.…”
Section: / Qualité De La Viande En Lien Avec Son Phunclassified